The role of artificial intelligence in supporting student learning and improving communication between parties to the educational process and the challenges of its application: metaverse technology as a model (Journal of Academic Research, 2024)
The current study aims to clarify the role of metaverse technology in supporting student learning and enhancing communication and active participation among parties to the educational process, as it provides classrooms through life-like ecosystems and motivates students to interact with their colleagues and teachers, This study comes in light of the changes taking place in educational systems today. There is a growing trend in education to integrate modern technologies and practices in order to improve the comprehensive educational experience, and to adopt new methods that motivate the learner to engage in building his knowledge to be the focus of the educational process. Educational systems also need to focus on On the needs of 2023 and beyond, Looking at new methods of learning that are compatible with technological transformation, and highlighting the challenges of its application in order to prepare to face them. In its approach, the study adopted the descriptive, desktop-documentary method with the aim of collecting data from some literature, previous studies, and relevant scientific references, to find an accurate description of the phenomenon, in a way that achieves the objectives of the study and answers its questions. The study presents a set of recommendations, the most important of which is including metaverse technology as an independent course within the study curricula to keep pace with the virtual revolution that has added new dimensions to interactive education.
Keywords: Metaverse Technology; The Educational Proces